Policy factors of gender inequalities in migration flows. The case of Romanian Roma in Italy and Spain - Vlase, Ionela (Calitatea Vieții, 2022)
Romanian migration flows knew a tremendous increase after the fall of communism in 1989. However, Romanian citizens didn’t participate to migration process to the same extent, irrespective of their age, gender or ethnicity. Important inequalities affect migrants’ profiles. This paper will highlight inequalities particularly with respect to gender and ethnic dimensions of Romanians participating in the process of labour migration. Main destination countries of Romanian migrants are Italy and Spain. These receive almost two thirds of Romanians abroad. Based on bivariate analyses carried out on data from EU-inclusive survey 2011, it is shown that Romanian Roma’s access to resources enabling migration after 1990 was influenced by gender. A particular attention will be paid to the gender inequalities among Roma migrants pertaining to differences in education, access to jobs, and attribution of caretaking roles by virtue of their gender norms, further revealing the vulnerability of Roma women with respect to their access to global labour market and to social services in the destination countries. Furthermore, policies toward immigrants also affect differently these migrant groups across countries of destination.